Threat or Corrective? Assessing the Impact of Populist Parties in Government on the Qualities of Democracy: A 19-Country Comparison. Issue 4 (6th October 2022) - Vittori, Davide
Abstract: Scholars have long debated whether populism harms or improves the quality of democracy. This article contributes to this debate by focusing on the impact of populist parties in government. In particular, it inquires: (1) whether populists in government are more likely than non-populists to negatively affect the quality of democracies; (2) whether the role of populists in government matters; and (3) which type of populism is expected to negatively affect the quality of liberal-democratic regimes. The results find strong evidence that the role of populists in government affects several qualities of democracy. While robust, the findings related to (2) are less clear-cut than those pertaining to (1). Finally, regardless of their role in government, different types of populism have different impacts on the qualities of democracy. The results show that exclusionary populist parties in government tend to have more of a negative impact than other forms of populism.